1989
DOI: 10.1111/j.1432-1033.1989.tb15158.x
|View full text |Cite
|
Sign up to set email alerts
|

A distinct form of ribonuclease H from calf thymus stimulates its homologous DNA‐polymerase‐α–primase complex

Abstract: A ribonuclease H which degrades RNA specifically in K N A-DNA hybrids and, moreover, stimulates its homologous DNA-polymerase-primase complex was purified from calf thymus. The enzyme consists of a single polypeptide of molecular mass 78 kDa. It requires divalent cations for activity, and prefers MgZ+ over Mn2+.Ribonuclease H is optimally active at neutral pH and in 75 mM potassium acetate and is strongly sensitive to N-ethylmaleimide.[3H]Poly(rA) . poly(dT), [3H]poly(rC) . poly(dI), and [3H]KNA . MI 3-DNA are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Two classes of RNase H, RNase HI and II, have been identified in a variety of eukaryotes, purified and characterized (1)(2)(3)(4)(5)(6)(7)(8) as a cofactor. Both forms of RNase H randomly degrade RNA in long RNA͞DNA hybrid structures (2,9).…”
mentioning
confidence: 99%
“…Two classes of RNase H, RNase HI and II, have been identified in a variety of eukaryotes, purified and characterized (1)(2)(3)(4)(5)(6)(7)(8) as a cofactor. Both forms of RNase H randomly degrade RNA in long RNA͞DNA hybrid structures (2,9).…”
mentioning
confidence: 99%
“…In our recent work we have purified and characterized many replicative proteins from calf thymus glands, including the DNA-polymerase-a -primase complex [13,141, the DNA polymerases 6 and F [I 51, a polymerase-a-stimulating ribonuclease H [16], DNA topoisomerases [17], and two DNA helicases [I 81. Because of the species-specific interaction between SSB and polymerase a and probably other components of the replicative apparatus as well, we attempted to purify SSB from bovine tissue.…”
mentioning
confidence: 99%
“…The accessibility of anti-sense ONs to intracellular mRNA, however, will be different from that to isolated RNA in vitro, because mRNAs interact with many protein factors and form secondary and tertiary structures in vivo. Heidenreich et al (1995) reported the enhancement of the ribozyme activity in isolated nuclei and thought that it was due to protein factors that protect and help ribozymes annealing to target RNA, such as hnRNP A1 and HIV-1 NC7 protein. Although we only surveyed a 40-ntd region of AML1-MTG8 mRNA adjacent to the fusion point, this region was effectively digested with endogenous RNase H by the addition of anti-sense ONs in nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, RNase HII might be responsible for the anti-sense effect. In addition to these two classes of RNase H enzymes, another distinct form of RNase H has been puri®ed from calf thymus as a stimulating factor of DNA polymerase a-primase activity (Hagemeier & Grosse 1989). This enzyme consists of a single polypeptide of 78 kDa, requiring divalent cations for activity (preferring Mg 2 to Mn 2 ), and is strongly sensitive to NEM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation